2021
DOI: 10.1186/s43556-021-00050-3
|View full text |Cite
|
Sign up to set email alerts
|

Computationally repurposed drugs and natural products against RNA dependent RNA polymerase as potential COVID-19 therapies

Abstract: Repurposing of existing drugs and drug candidates is an ideal approach to identify new potential therapies for SARS-CoV-2 that can be tested without delay in human trials of infected patients. Here we applied a virtual screening approach using Autodock Vina and molecular dynamics simulation in tandem to calculate binding energies for repurposed drugs against the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp). We thereby identified 80 promising compounds with potential activity against SARS-Cov2, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
(58 reference statements)
2
17
1
Order By: Relevance
“…Our earlier studies predicted sertindole to be a strong binder to SARS-CoV-2 RdRp [ 6 , 7 ], and the activity of sertindole against M pro also was later reported by Vatensever et al [ 44 ].…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Our earlier studies predicted sertindole to be a strong binder to SARS-CoV-2 RdRp [ 6 , 7 ], and the activity of sertindole against M pro also was later reported by Vatensever et al [ 44 ].…”
Section: Resultsmentioning
confidence: 70%
“…Potential conivaptan binding to the SARS-CoV-2 nsp9 replicase was found by Chandel et al using a combination of Autodock screening followed by MD simulations [ 30 ]. Several other recent computational studies have also reported potential binding of conivaptan to various SARS-CoV-2 targets (see summary in Piplani et al) [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the face of the COVID-19 pandemic, a huge increase of interest in RdRp was observed, as it is an important therapeutic target in RNA virus-caused diseases, including SARS-CoV-2. For this reason, many known RdRp inhibitors (such as described in this paragraph dasabuvir [ 114 ], pimodivir [ 115 ], radalbuvir [ 116 , 117 ] and tegobuvir [ 118 ]) have been also included in the research of an effective drug for COVID-19. Elfiky and colleagues [ 119 ] made attempts to assess the possibility of using several antiviral drugs or drug candidates (including setrobuvir and mentioned earlier galidesivir) for the treatment of SARS-CoV-2 virus infections (in silico drug-repurposing).…”
Section: Molecular Mechanisms Of Action Of Non-nucleoside Structured Compoundsmentioning
confidence: 99%